Towards a Regulation on Artificial Intelligence (AI): Key Considerations and International Regulations - Bustillos Ortega, Olda (2024)
Artificial Intelligence (AI) is a disruptive technology that has a significant impact on various aspects of society and the economy. Its rapid development has generated an urgent need to define and establish regulations that address the ethical, social and economic challenges that come with its adoption. The lack of adequate regulation carries the risk of discrimination and bias in AI-based decision-making, which could undermine public trust in this technology. This article aims to identify the key elements necessary to serve as a basis for the development of effective AI regulations. International regulations from the European Union, the United States, as well as initiatives from international organizations such as UNESCO, the OECD and the Economic Commission for Latin America (ECLAC) with its ILIA AI Strategy Index are taken into account. In addition, the specific case of Costa Rica is presented as an example of the formulation of an Artificial Intelligence Strategy. Guidelines are proposed for coherent and effective AI regulations that promote cooperation and harmonization of regulations. These guidelines are offered as a guide to regulate AI tools and applications, as well as to adopt and use them responsibly for the benefit of society supported by cooperation, consensus and agreements between organizations and countries.